Pengaruh Good Corporate Governance terhadap Kinerja Keuangan pada Perusahaan Sektor Healthcare di BEI Tahun 2020-2024 - Azzahra Keisha Ramadhani; Maylinda Awalin; Aprilia Saputri; Muhammad Faris Ghozi; Ma’rifatul Ummah; Tiara Salsabila; Rohmawati Kusumaningtias; Ambar Kusumaningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study investigates the influence of Good Corporate Governance (GCG) on the financial performance of healthcare companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The healthcare sector faces increasing demands for transparency, accountability, and effective governance in the post-pandemic era, making financial performance an important issue for corporate sustainability. This research aims to examine the effect of independent commissioners and institutional ownership as proxies of GCG on financial performance measured by Return on Assets (ROA). The study employs a quantitative approach using panel data regression analysis with a purposive sampling technique. The sample consists of healthcare companies that consistently published complete financial reports during the observation period. The results indicate that independent commissioners have a positive and significant effect on ROA, reflecting the importance of effective supervisory functions in improving operational efficiency and corporate performance. Meanwhile, institutional ownership shows a positive but insignificant effect on ROA, indicating that institutional investors have not fully contributed to strengthening managerial monitoring. Simultaneously, both variables significantly affect financial performance. These findings highlight the importance of implementing effective corporate governance practices in the healthcare sector.